ผลของการพัฒนาวิชาชีพครูโดยใช้หลักวิธีการสอนสำหรับผู้ใหญ่ร่วมกับระบบการเรียนรู้จำเพาะบุคคล - Chaipidech, Pawat; Kajonmanee, Tanachai; Chaipah, Kornchawal; Srisawasdi, Niwat (วารสารหน่วยวิจัยวิทยาศาสตร์ เทคโนโลยี และสิ่งแวดล้อมเพื่อการเรียนรู้ (Journal of Research Unit on Science, Technology and Environment for Learning), 2021)
Effectiveness of Andragogical Teacher Professional Development Program with Integration of Personalized Learning System Pawat Chaipidech, Tanachai Kajonmanee, Kornchawal Chaipah and Niwat Srisawasdi รับบทความ: 27 เมษายน 2564; แก้ไขบทความ: 14 กรกฎาคม 2564; ยอมรับตีพิมพ์: 16 กรกฎาคม 2564; ตีพิมพ์ออนไลน์: 29 พฤศจิกายน 2564 บทคัดย่อ ด้วยแรงโหมกระหน่ำของเทคโนโลยีดิจิทัลสำหรับการจัดการศึกษาในยุคนี้นั้น บทบาทของครูจำเป็นต้องปรับเปลี่ยนโดยไม่ใช่เป็นเพียงแค่การผู้นำส่งความรู้เนื้อหาสาระหลักให้นักเรียนเท่านั้น แต่จะต้องปรับตนให้รู้ในการใช้เทคโนโลยีสมัยใหม่และเทคนิควิธีการสอนที่เป็นการประยุกต์ใช้เทคโนโลยีเป็นเครื่องมือในการปฏิบัติงานการสอนเนื้อหาจำเพาะ ปัจจุบันในบริบทงานทางด้านวิทยาศาสตร์ศึกษามีความจำเป็นเร่งด่วนในการพัฒนาโปรแกรมการฝึกอบรมเพื่อการพัฒนาวิชาชีพครูเพื่อการเปลี่ยนรูปองค์ความรู้และชุดทักษะใหม่ที่จำเป็นต่อการปฏิบัติงานการสอนผ่านกรอบคิดเกี่ยวกับความรู้ในการสอนจำเพาะเนื้อหาโดยใช้เทคโนโลยี (TPACK) โดยเฉพาะการฝึกอบรมที่พิจารณาถึงประสบการณ์การปฏิบัติงานการสอนที่แตกต่างกัน ดังนั้นการวิจัยนี้มุ่งออกแบบและพัฒนาโปรแกรมการฝึกอบรมเพื่อการพัฒนาวิชาชีพครูโดยอิงหลักวิธีการสอนสำหรับผู้ใหญ่เพื่อสร้างเสริม TPACK ในกลวิธีสะเต็มศึกษาบูรณาการ ให้สำหรับครูวิทยาศาสตร์ประจำการ จำนวน 89 คน ที่เข้าร่วมในโครงการโครงการพัฒนาสมรรถนะนักเรียนระดับมัธยมศึกษาด้วยนวัตกรรมเคเคยูสมาร์ทเลิร์นนิ่ง (KKU–SLA) และระบบการเรียนรู้แบบจำเพาะบุคคลได้ถูกนำมาใช้เป็นส่วนสำคัญหนึ่งของโปรแกรมการฝึกอบรมนี้เพื่อการตอบสนองต่อความจำเป็นในการเรียนรู้ผ่านการฝึกอบรมอย่างจำเพาะของแต่ละบุคคล โดยมีครูประจำการจำนวน 2 กลุ่มที่เข้ารับการฝึกอบรมผ่านโปรแกรมการฝึกอบรมที่นำเสนอใหม่นี้ กลุ่มแรกเป็นกลุ่มครูที่ไม่มีประสบการณ์การจัดการเรียนรู้ดิจิทัล จำนวน 28 คน และได้รับโปรแกรมการฝึกอบรมแบบเผชิญหน้าประสานเวลา ส่วนอีกกลุ่มเป็นกลุ่มครูที่มีประสบการณ์การจัดการเรียนรู้ดิจิทัล จำนวน 61 คน และได้รับการฝึกอบรมแบบออนไลน์ประสานเวลา เนื่องด้วยอยู่ในช่วงการแพร่ระบาดของโรคโควิด–19 ซึ่งครูทั้งสองกลุ่มถูกประเมิน TPACK ทั้งก่อนและหลังการเข้าร่วมในโปรแกรมการฝึกอบรม จากการวิเคราะห์ข้อมูลโดยใช้สถิติ Wilcoxon sign–rank test และ paired t–test พบว่า คะแนน TPACK รวมของครูทั้งสองกลุ่มเพิ่มขึ้นอย่างมีนัยสำคัญทางสถิติเช่นเดียวกันกับคะแนนในด้านความรู้ในเทคโนโลยี (TK) และคะแนนความรู้ในการใช้เทคโนโลยีสนับสนุนเนื้อหา (TCK) จากผลการวิจัยแสดงให้เห็นว่าโปรแกรมการฝึกอบรมที่พัฒนาขึ้นนี้สามารถเป็นทางเลือกหนึ่งในการพัฒนาวิชาชีพครูวิทยาศาสตร์สำหรับชั้นเรียนวิทยาศาสตร์ปัจจุบันนี้ได้ แต่ในขณะเดียวกันก็มีส่วนที่สามารถพัฒนาต่อยอดเพื่อการนำไปสู่ผลของการพัฒนาคุณภาพ TPACK ได้เช่นกัน คำสำคัญ: หลักวิธีการสอนสำหรับผู้ใหญ่ การพัฒนาวิชาชีพครู ความรู้ในการสอนจำเพาะเนื้อหาโดยใช้เทคโนโลยี การเรียนรู้จำเพาะบุคคล การเรียนรู้แบบดิจิทัล Abstract With the bombardment of digital technology in today’s educational institutions, the role of teachers is constantly changing. Teachers are required to not only deliver the core subject content knowledge but also update their knowledge of modern technology and pedagogical techniques, which demand the integration of digital technology in specific content teaching. In the context of science education, there is a call for a specific and effective teacher professional development (TPD) program to improve science teachers’ essential knowledge and facilitate the acquisition of new sets of skills to succeed in technology–enhanced classrooms. The Technological Pedagogical and Content Knowledge (TPACK) framework has a critical role in promoting the teaching knowledge transformation of professional teachers, particularly regarding the differences in their teaching experience. This study intended to design an andragogical TPD program that particularly addressed the TPACK framework of integrated Science, Technology, Engineering, and Mathematics (STEM) education for the training of 89 in–service science teachers in the Khon Kaen University Smart Learning Academy (KKU–SLA) project. To specialize the proposed TPD program, a personalized ubiquitous learning system produced by KKU–SLA was employed to personalize the individual training need for the teachers. The participants consisted of two groups: the first group included 28 novice teachers with non-digital teaching experience who attended a face-to-face TPD program; the second group included 61 expert teachers with digital experience who attended an online TPD program due to the Coronavirus Disease 2019 (COVID–19) pandemic. Both groups were characterized by the proposed TPD regarding their different teaching backgrounds, as previously mentioned, and they were examined based on their TPACK before and after the specific training intervention. Based on the Wilcoxon sign–rank test and paired t–test statistical analyses, the results revealed that the total TPACK scores of both groups of teachers, as well as their technological knowledge (TK) and technological content knowledge (TCK) had been improved significantly. According to the results, the study suggested that the proposed TPD program could be an alternative way to promote teacher’s essential teaching knowledge for today’s science classes and that there is a call to improve the program to gain better results for their TPACK comprehension. Keywords: Andragogy, Teacher professional development, TPACK, Personalized learning, Digital learning